Possible evidence of delocalized excitons in Cr-doped PrFeO3: An experimental and theoretical realization. (July 2019) - Kumar, Anil; Mishra, Vikash; Warshi, M. Kamal; Sati, Aanchal; Sagdeo, Archna; Kumar, Rajesh; Sagdeo, P.R.
Abstract: Here we introduce a way to understand the phenomena of localization/delocalization of excitons experimentally as well as by first-principle study. Using in-situ temperature-dependent optical absorption spectroscopy (TD OAS), variation of delocalization parameter (ξ) and electronic disorder in terms of Urbach energy as a function of temperature was estimated. For this purpose, polycrystalline samples of PrFe1−x Crx O3 (x = 0 to 0.25) were synthesized via wet chemical method. The ξ increased with inclusion of Cr doping, which could be understood in terms of an increase in delocalized nature of excitons. Further, the theoretically simulated optical absorption spectrum for undoped and Cr-doped PrFeO3 clearly indicated the change in excitonic peak from almost Gaussian to Lorentzian nature and was explained in terms of an increase in delocalized nature of excitons with inclusion of Cr doping. Thus, using the combination of TD OAS and first-principle calculations, we demonstrated a way to acquire precise information about exciton dynamics, which could be very helpful in understanding many interesting phenomena such as electron–phonon coupling, electronic disorder near band edge and transport properties. Highlights: A careful analysis of temperature dependence behavior of Urbach energy was used to understand exciton–phonon coupling. The change in excitonic peak shape from almost Gaussian to Lorentzian nature with Cr doping in PrFeO3 hints delocalization of excitons. Using a combination of temperature dependent optical absorption spectroscopy and simulation, we demonstrated a way to acquire information about exciton dynamics.